Targeted protein degraders of SARS-CoV-2 Mpro are more active than enzymatic inhibition alone with activity against nirmatrelvir resistant virus - Baolong Pan; Simon J. Mountford; Maki Kiso; Danielle E. Anderson; Georgina Papadakis; Kate E. Jarman; Danielle R. Tilmanis; Belinda Maher; Thomas Tran; Jake Shortt; Seiya Yamayoshi; Yoshihiro Kawaoka; et al. (Communications Medicine)
Abstract Background Effective antiviral therapy is lacking for most viral infections, and when available, is frequently compromised by the selection of resistance. Targeted protein degraders could provide an avenue to more effective antivirals, able to overcome the selection of resistance. The aim of this study was to determine whether adaptation of SARS-CoV-2 main protease (Mpro, also described as chymotrypsin-like protease (3CLpro) or non-structural protein 5 (Nsp5)) inhibitors into degraders leads to increased antiviral activity, including activity against resistant virus. Methods We adapted the clinically approved Mpro inhibitor nirmatrelvir into a panel of degraders. Size-matched non-degrading controls were also synthesised to discriminate degradation activity from inhibition activity. Degrader activity was confirmed using an inducible Mpro-HiBiT tag expressing cell line. Antiviral activity against both wildtype and nirmatrelvir-resistant virus was performed using infection of susceptible cell lines. Results Here we show three compounds, derived from nirmatrelvir and utilising VHL or IAP ubiquitin ligase recruiters, capable of degrading Mpro protein in a concentration, time and proteasome dependent fashion. These compounds also degrade nirmatrelvir-resistant mutant Mpro. The most potent of these compounds possesses enhanced antiviral activity against multiple wildtype SARS-CoV-2 strains and nirmatrelvir-resistant strains compared to non-degrading controls. Conclusions This work demonstrates the feasibility of generating degraders from viral protein inhibitors, and confirms that degraders possess higher antiviral potency and activity against resistant virus, compared to size matched non-degrading enzymatic inhibitors. These findings further support the development of targeted viral protein degraders as antiviral drugs, which may lead to more effective antiviral therapies for the future.